Regioregularity controlled phase behavior for Poly(3-hexylthiophene): A combined study of simple coarse-grained simulation and experiment. (12th September 2019) - Kim, Hyeong Jun; Kim, Jin-Seong; Kim, Youngkwon; Jung, Yeon Sik; Kim, Bumjoon J.; Kim, YongJoo
Abstract: In this study, we developed a simple coarse-grained simulation model framework to investigate the effect of regioregularity (RR) on the crystallization behavior of poly(3-hexylthiophene) (P3HT). To describe the regio-chemistry of P3HT, two different coarse-grained beads were designed to contain either regio-regularly substituted head-to-tail (HT) orientations or regio-irregularly substituted non-HT orientations, and two beads were randomly incorporated in a single polymer where the total RR was tuned from regio-random (RR = 50%) to regio-regular (RR = 100%). Based on our modeling, the crystallization behaviors in both bulk and solution states were investigated. As the number of irregularly substituted non-HT orientations increased, crystallization temperature in the bulk shifted to a lower temperature. When the RR of P3HT was lower than a critical RR value, which was 72.2% in our study, the crystallization of the P3HT chains was eventually suppressed. In the solution state, most of high RR P3HT chains stacked in parallel to produce nanowire (NW) structure to maximize the number of π-stackings in the system, whereas the P3HTs formed a globule structure when the RR value decreased below critical RR. To experimentally validate our simulation results, we synthesized a series of P3HTs having precisely controlled RRs from 66% to 95% with comparable molecular weights to the simulation. Well-matched experimental results suggested that our simplified model provides efficient computational guidance to describe the RR effect on crystalline feature of P3HTs for the various possible applications in organic optoelectronics. Graphical abstract: Image 1 Highlights: Simple coarse-grained model is developed to describe the effect of regioregularity (RR) on crystallization of P3HT. Experimental validation with a series of P3HTs having a wide range of RR from 66% to 95% is followed. Our model predicts critical RR value for crystallization of P3HT in bulk and solution.